1990
DOI: 10.1073/pnas.87.23.9459
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for coiled-coil dimer formation by an Epstein-Barr virus transactivator that lacks a heptad repeat of leucine residues.

Abstract: Two regions of the Epstein-Barr virus (EBV) BZLF1 gene product, ZEBRA, share sequence homology with c-Fos, one of which corresponds to the DNA binding domain of c-Fos. ZEBRA does not, however, contain the heptad repeat of leucines present in the dimerization domains of leucine zipper proteins. Here it is shown that ZEBRA binds its recognition sites as a homodimer and that the region adjacent to the basic DNA binding domain is essential for dimerization. This region contains a 4-3 repeat of predominantly hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 22 publications
(14 reference statements)
1
90
1
Order By: Relevance
“…protein in surface gene expression. The autoregulatory function of the protein in its own promoter has been observed in a number of genes (49,50). In our study, we found that M protein can transactivate the CCAAT box of the major S promoter to regulate surface expression of L, M, and S proteins.…”
Section: Protein Regulates Surface Gene Expression By Interacting Wmentioning
confidence: 59%
“…protein in surface gene expression. The autoregulatory function of the protein in its own promoter has been observed in a number of genes (49,50). In our study, we found that M protein can transactivate the CCAAT box of the major S promoter to regulate surface expression of L, M, and S proteins.…”
Section: Protein Regulates Surface Gene Expression By Interacting Wmentioning
confidence: 59%
“…39,40 It is encoded by EBV IE gene BZLF1 and composed of 245 amino acids. The molecular structure of Zta consists of five functional regions: a transcriptional activation domain (aa 1-167) located in the amino terminus of the protein, [41][42][43] a putative regulatory domain (aa 168-177) containing a major phosphorylation site S-173 required for viral replication, 44 a basic DNA binding domain (aa [178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194]) that determines the specificity of DNA recognition and directly interacts with DNA sequence elements, 33,37,45 a coiled-coil domain (aa 195-227) responsible for homodimerization and an accessory activation domain (aa 228-245) in the carboxy terminus.…”
Section: Characterization Of Ztamentioning
confidence: 99%
“…Zta is in the bZip class of transcription factors (Farrell et al 1989;Chang et al 1990;Flemington and Speck 1990;Lieberman and Berk 1990)• The Zta amino-terminal activation domain is neither acidic nor significantly enriched in any one type of amino acid residue (Giot et al 1991;Lieberman and Berk 1991). With a template containing a TATA box and seven upstream Zta-binding sites, purified Zta stimulated transcription -10-fold in reactions reconstituted with either phosphocellulose D fraction or eTFIID complex (Fig.…”
Section: The Etfiid Complex Mediates Activation By Diffent Classes Ofmentioning
confidence: 99%